Therapeutically (Un)Just Interactions in Family Court Proceedings - Dollar, Cindy Brooks (Criminal justice policy review, 2020)
Court systems have a unique and powerful impact on the lives of persons who enter into them. In recognition of some of the deleterious effects of traditional court models, scholars and practitioners advocate for alternative court processes, especially through the implementation of specialty courts. Family court is a type of specialized court, which handles legal disputes among family members. The stated mission of family courts reflects notions of therapeutic jurisprudence; however, scarce research examines if therapeutic jurisprudence is actually practiced in family court settings. Using 12 months of observational data of over 100 hearings, the present study assesses the extent to which principles of therapeutic jurisprudence are apparent in court proceedings. I find that although therapeutically just interactions are common in family court, some encounters remain antitherapeutic or damaging. The implication of family court’s current operation within the broader “justice” system is discussed.